How large banks use CDS to manage risks: bank-firm-level evidence - Iftekhar Hasan; Deming Wu (Bank of Finland, 2016)
​We test five hypotheses on whether banks use CDS to hedge corporate loans, provide credit enhancements, obtain regulatory capital relief, and exploit banking relationship and private information. Linking large banks' CDS positions and syndicated lending on individual firms, we observe strong evidence for the credit enhancement and regulatory capital relief hypotheses, but mixed evidence for the hedging, banking relationship, and private information hypotheses. Banks buy and sell more CDS on their borrowers, but their net CDS positions and lending status are largely unrelated. We find no evidence of bank using CDS to exploit private information.
URN:NBN:fi:bof-201604291112
Keywords: G14; G21; G23; G28; G32; 330